Prospects for University’s Open Educational Resources - Тю V. Dneprovskaya; I. V. Shevtsova (Высшее образование в России)
The purpose of the study is to identify and justify the modern perspectives of open educational resources (OER) for higher education in Russia. The methodology includes study of initiatives, services, OER tools in Russia and abroad, evaluation of OER development factors. The authors have conducted a survey of university lecturers, processing of the results using statistical methods of analysis. The following prospects for the development and use of OER in higher education are identified: 1) further dissemination of free access to educational materials through the involvement of a wider range of universities; 2) improving the quality of educational materials in the context of expanding access to them; 3) extension of electronic educational environment, since OER are not tied to specific tools or technologies, and may be distributed in social media, mobile applications. The study of international and Russian practice has shown that OER provide methodological support primarily to university lecturers, allowing them to study the best practices of education leaders, to handle OER in accordance with the educational objectives of their courses and the students’ requirements and expectation. As a result of the survey, it was found that 60% of lecturers at Russian universities distribute their own educational materials on the Internet during the educational process for the convenience of students.